2022
DOI: 10.3390/genes13061033
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Non-Coding RNA in the Growth and Development of Skeletal Muscle in Domestic Chickens

Abstract: Chicken is the most widely consumed meat product worldwide and is a high-quality source of protein for humans. The skeletal muscle, which accounts for the majority of chicken products and contains the most valuable components, is tightly correlated to meat product yield and quality. In domestic chickens, skeletal muscle growth is regulated by a complex network of molecules that includes some non-coding RNAs (ncRNAs). As a regulator of muscle growth and development, ncRNAs play a significant function in the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…LncRNA is a new type of regulatory RNA, which is a ncRNA with a length of more than 200 bp. LncRNA is an important component of ncRNA ( Shi et al, 2022 ), and it plays an essential role in goat ovulation and kidding mainly by regulating transcription and post-transcription ( Lian et al, 2020 ). LncRNA also plays an important role in the regulation of the fertility network.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA is a new type of regulatory RNA, which is a ncRNA with a length of more than 200 bp. LncRNA is an important component of ncRNA ( Shi et al, 2022 ), and it plays an essential role in goat ovulation and kidding mainly by regulating transcription and post-transcription ( Lian et al, 2020 ). LncRNA also plays an important role in the regulation of the fertility network.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many target mRNAs of DE lncRNAs were enriched in GO terms such as myofibril assembly, muscle fiber development, striated muscle contraction, M band, and muscle cell development. Many target mRNAs of DE miRNAs were enriched in the GO terms related to morphogenesis; the reason could be that during embryonic muscle development, the myogenic progenitor cells derived from the myotome continue to migrate and proliferate to the limbs, thereby promoting limb morphogenesis ( Shi et al, 2022 ). These results suggested that the muscle had changed dramatically at E14 compared to E10 after continuous growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their length, function, and structural characteristics, ncRNAs can be divided into microRNAs (miRNAs), long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and others (Hombach and Kretz, 2016). Currently, an increasing number of studies have demonstrated the close relationship between miRNAs and lncRNAs in the development process of poultry skeletal muscle, including myoblast proliferation, differentiation, apoptosis, as well as myofiber maturation and hypertrophy (Li et al, 2016;Shi et al, 2022). Additionally, more attention has been paid to the competing endogenous RNA (ceRNA) hypothesis.…”
Section: Introductionmentioning
confidence: 99%